The feasibility of occupational therapy visual art groups for children (8 – 12 years) with learning differences in a low-resource setting in the Western Cape, South Africa - Conolly, Naomi Beth (Stellenbosch : Stellenbosch University, 2024)
Thesis (MOccTher)--Stellenbosch University, 2024.